Assessment of food safety knowledge, attitude and practices among food handlers in restaurants, Putrajaya, Malaysia - Ab. Hamid, Rosnani (2015)
Inappropriate food handling is the main contributing factor often associated with the food borne outbreak and thousands of millions of people around the globe fall ill and many die as a result of eating unsafe food. The incidence or the number of food poisoning cases reported is increasing in Malaysia and statistics showed that in 2002 the incidence rate of such disease is only 23.1 per 100,000 populations; comparably in 2011 it has increased to 56.25 per 100,000 populations.The aim of this study is to evaluate the level of knowledge, attitude and practice on food safety among food handlers working in restaurants in Putrajaya, Malaysia. A total of 127 food handlers were randomly selected from 23 restaurants and the data collected in October2013 through self-administered questionnaires was analyzed using the SPSS Version 16. The respondents comprising of 36% or 46 Malaysians and 63.8% or 81 were nonMalaysians, of which 38.6% or 49 had attended food hygiene training program before being engaged in food business. Generally the food safety knowledge was good with the mean score 90.3 ± 7.78. However, respondents‘ lack of knowledge related to reheating of cooked food (75.1 ± 25.66) and the safe temperature of cooked food (71.9 ± 33.54). Knowledge differed significantly by age groups (F=2.530; p=0.044). Respondents had a positive attitude about food safety with mean score 93.9 ± 6.81, although there were significant differences between trained and untrained workers (t=2.406; p=0.018), Malaysian ethnic groups (F=2.502; p=0.034), Malaysians and nonMalaysians (t=3.273; p=0.001) and due to differences in education levels (F=6.057; p=0.003). The mean score for practice was 92.9 ± 7.64 and again there were significant differences related to education levels (F=1.345; p=0.003), gender (t=-2.120; p=0.036) and ethnicity of Malaysian workers (F=2.502; p=0.034). This study revealed that a strong relationship was found between knowledge and attitude on food safety (r=0.26; p=0.002) and between knowledge and practice (r=0.0203; p=0.022). In summary, this study suggests that food workers in Putrajaya displayed good knowledge, a positive attitude and an excellent practiceon food safety. Yet results showed that food workers are still lacking in basic knowledge on food safety, particularly on reheating and safe temperature of cooked food. As a conclusion, this study can be used as a stepping stone for other researchers to embark on studies concerning food safety in Putrajaya. It is hoped this study will bring about positive managerial implications where the relevant health authority is able to utilize the information to develop more effective strategies towards improving the food safety in the Federal Administrative Centre, in ensuring that food sold, served and consumed in restaurants are not only safe but most importantly, the food borne diseases can be prevented in Putrajaya.